Los sistemas de control interno y su repercusión en el desarrollo competitivo de las empresas comerciales afiliadas a la cámara de comercio del cantón Quevedo, año 2010 - Águila Vera, Blanca Alexandra (2012)
This research explores the sources of influence on the activities of commercial companies affiliated to the Chamber of Commerce of Quevedo, referencing not have adequate control of their administration and accounting. Within this context, seeks to answer the following research question: What is the incidence of internal control systems in the competitive development of commercial enterprises affiliated to the Chamber of Commerce of Quevedo Canton? The general objective for this research was wont; determine the incidence of internal control systems in the competitive development of commercial enterprises affiliated to the Chamber of Commerce of the Canton Quevedo, to propose the design of a manual of internal control over commercial enterprises affiliated to the Chamber of Commerce of Quevedo. In this way and by hypothesis was evident that the failure to implement internal control systems negatively affects the competitive development of commercial enterprises, mainly in administrative and accounting processes. Moreover unknown commercial enterprises activities the Chamber of Commerce of Quevedo, however ask to be trained in business skills, which represents an opportunity for the institution to expand their horizons by hosting a trade group little favored. As main recommendations arise manage the design of a manual internal control over business enterprises affiliated to the Chamber of Commerce of Quevedo, to include the main structure and orientation process that encourages traders to improve their overall development business.